Some philological problems in the "Miracles" of Gabra Manfas Qeddus - Marrassini, Paolo (Aethiopica, 2000)
The philological examination of the genealogical tree of the “Miracles” of Gabra Manfas Qeddus, based of course on the principle of conjunctive errors and not on that of marginal similarities, has shown two important phenomena: 1. that not just one, but at least six different stemmas (for miracles I, II‑VII, VIII, IX, X‑XIII) can be identified; and 2. that none of these stemmas has the slightest relationship with those already identified for the “Life”. This involves an important historical consequence, because it demonstrates the profound difference, which has always been supposed in hagiography, between the redaction of the “Life” and that of the “Miracles” of the same saint.